The influence of short-term thermo-mechanical densification on the surface wettability of wood veneers - Bekhta, Pavlo; Krystofiak, Tomasz (Maderas. Ciencia y Tecnología, 2016)
The study investigated the effects of short-term thermo-mechanical (STTM) densification temperature and pressure on changes in surface wettability of alder (Alnus glutinosa), beech (Fagus sylvatica), birch (Betula verrucosa) and pine (Pinus sylvestris) wood veneer. Veneer sheets were densified using pressure levels of 4 MPa, 8 MPa and 12 MPa at three temperatures: 100°C, 150°C and 200°C for a short time of 4 min. Wettability was determined by measuring contact angles with distilled water. The results were compared with those of non-densified veneers. The results showed that in a relatively short process time wettability can be changed significantly. The wettability analysis showed that STTM-densified veneer surfaces became more hydrophobic, which indicates poor wettability. However, it was found that even STTM densification of veneers provides stable properties; in particular, contact angle values were stable for 24 hours after densification, which is an important consideration for industrial applications. The effect of temperature on the contact angle was more evident than that of pressure. Linear correlations were found between contact angle and both mass loss and compression ratio for all investigated wood species. These findings may be used to provide initial data for adhesive/ coating application processes in woodworking industry.